2019
DOI: 10.1080/0284186x.2019.1578410
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk factors for cancer-related cognitive impairment: a systematic review

Abstract: Background: Cancer-related cognitive impairment (CRCI) is a commonly reported complaint among non-CNS cancer patients. Even subtle CRCI may have detrimental effects on quality of life and identifying patients at increased risk for CRCI to improve survivorship care is important. In the present paper, we systematically reviewed available studies of possible genetic risk factors for developing CRCI. Methods: Keyword-based systematic searches were undertaken on 24 July 2018 in PubMed, Web of Science, The Cochrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 37 publications
(110 reference statements)
0
18
2
1
Order By: Relevance
“…www.nature.com/scientificreports/ The potential for genetic polymorphisms to modulate the impact of neurologic insults has been identified in several diseases 79,80 , but is not defined in cancer. Recent systematic review has found variable correlations between genetic polymorphisms and CRCI 81 , precluding the conclusive definition of a relationship. Connectomics provides a novel contribution to elucidating this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificreports/ The potential for genetic polymorphisms to modulate the impact of neurologic insults has been identified in several diseases 79,80 , but is not defined in cancer. Recent systematic review has found variable correlations between genetic polymorphisms and CRCI 81 , precluding the conclusive definition of a relationship. Connectomics provides a novel contribution to elucidating this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…CRCI was not found to be associated with the genes coding IL-6, TNF, IL-1β, and brain-derived neurotrophic factor (BDNF). Except for APOE 4, genetic risk factors were not widely investigated (93). In general, the evidence is limited for possible genetic risk factors for CRCI, but we can reach a consensus that genetic factors are associated with cognitive impairment in cancer patients after treatment.…”
Section: Genesmentioning
confidence: 99%
“…The methodological quality of the included studies was assessed based on the National Heart, Lung, and Blood Institute Quality Assessment Tool for Observational Cohort and Cross-sectional Studies and Quality Assessment for Controlled Intervention Studies (National Heart, Lung, and Blood Institute, 2019). In line with a previous study (Buskbjerg et al, 2019), item scores (yes/partly/no) were rated with points, that is, 1/0.5/0, respectively, and summed to get a total study quality score. A total prorated quality score was then generated for each included study by (a) dividing the total study quality score by the number of applicable items for the given study (this would generate a mean • • There was a significant between-subjects interaction, which indicated the beneficial effects of exercise training on cognitive function were independent of the BDNF genotype.…”
Section: Quality Assessment Of Included Studiesmentioning
confidence: 99%